1996
DOI: 10.1210/jcem.81.3.8772600
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-associated modulation of neuroendocrine counterregulation, hypoglycemia perception, and cerebral function in insulin-dependent diabetes mellitus: evidence for an intrinsic effect of insulin on the central nervous system.

Abstract: Evidence for an intrinsic effect of insulin on the central nervous system is accumulating. To test the hypothesis that insulin per se may modulate neuroendocrine counterregulation, hypoglycemia perception, and cerebral function in insulin-dependent diabetes mellitus, we examined 27 patients without any sign of classical autonomic neuropathy or evidence of so-called hypoglycemia unawareness. We used the hyperinsulinemic (0.67 vs. 2.00 mU/kg.min), stepped hypoglycemic (5.6/3.5/2.4/2.0 mmol/L) clamp technique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
3
21
0
2
Order By: Relevance
“…Circulating insulin appears to have no direct effect on glucose utilisation in the brain, despite recent observations in hypoglycaemic dogs and humans that the brain is sensitive to insulin [22,23]. In agreement with previous findings in dogs [24], brain glucose utilisation was of similar magnitude irrespective of the fall in circulating glucose from 4.8 to 2.4 mmol/l ( Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Circulating insulin appears to have no direct effect on glucose utilisation in the brain, despite recent observations in hypoglycaemic dogs and humans that the brain is sensitive to insulin [22,23]. In agreement with previous findings in dogs [24], brain glucose utilisation was of similar magnitude irrespective of the fall in circulating glucose from 4.8 to 2.4 mmol/l ( Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…With regard to responses to hypoglycemia, the evidence, although not uniformly in agreement, indicates that higher plasma insulin concentrations, which imply higher cerebral insulin concentrations, may elicit greater counterregulatory responses, increased symptoms, and deterioration of cognitive function to insulin-induced hypoglycemia (20). The best evidence for such conclusions is provided by Lingenfelser et al (19), who performed hyperinsulinemic stepped hypoglycemic clamps in subjects with type 1 diabetes. The results of our study, which might be related to a higher concentration of insulin detemir in the brain, fit well within this framework.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plasma concentrations of insulin detemir are greater than those of human insulin because of its binding to albumin (15) and because of its higher (four time) molar concentration than human insulin (16). This might directly influence counterregulatory responses because high plasma concentrations of insulin might modulate per se counterregulation to hypoglycemia (17)(18)(19)(20)(21)(22).The aim of the present study was to compare the physiological responses (counterregulatory hormones, symptoms, and impairment of cognitive function) to hypoglycemia induced by equipotent doses of insulin detemir and regular human insulin. Healthy subjects were studied during stan- …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of hypoglycemia, when the autonomic nervous system is activated, elevated insulin levels have been shown to inhibit (9), augment (10 -14), or not significantly effect (15)(16)(17)(18)) the sympathoadrenal response. Insulin may also alter the hypothalamicpituitary-adrenal response as noted by an insulin-mediated augmentation of the cortisol response to hypoglycemia that was significant in some (10,11,14) but not all (12,13,17,18) studies. Although the site of insulin action was not identified in these studies, it has been suggested that circulating insulin crosses the blood-brain barrier to directly activate the autonomic nervous system.…”
mentioning
confidence: 99%